The Correlation Between Handgrip Strength and Adductor Muscles with Muscle Mass, Fat Mass in the Elderly - Nur Luthfiatus Solikah; Awang Firmansyah; Nur Shanti Retno Pembayun; Hapsari Shinta Citra Puspita Dewi; Dhevano Taruna Putra Suhadak; Jose V Garcia Jimenez; Muhammad Reza Aziz Prasetya; Andika Bayu Putro (Physical Education Theory and Methodology)
Background. As you age, body composition will also change, with muscle mass decreasing and fat mass increasing. Handgrip strength and adductor muscle strength have been identified as indicators of older people’s health used to represent overall strength and muscle mass.